ANALISIS FAKTOR-FAKTOR YANG MENGHAMBAT KAJI ETIK PROTOKOL PENELITIAN: STUDI PADA KOMITE ETIK PENELITIAN FAKULTAS KEDOKTERAN UNIVERSITAS SEBELAS MARET, SURAKARTA - Susilawati, Tri Nugraha; Putri, Noviyati Rahardjo; Ardhi, Tunggul (Media Penelitian dan Pengembangan Kesehatan, 2024)
Ethics review is essential prior to conducting research involving humans and animals. This study aimed to evaluate the effectiveness of ethics review procedures and identify the causes of delayed ethical approval of the protocols submitted to Research Ethics Committee of the Faculty of Medicine, Universitas Sebelas Maret during 2022-2023. Retrospective data collected include protocol identity number, institution and educational level of the proposer, research type, date of protocol submission, completion of initial ethics review, and issuance of the ethical clearance certificate. A total of 458 protocols were received over 2 years period but the processing of 8 protocols were discontinued so that those 8 protocols were excluded from further analysis. Of the 450 protocols analysed, most involved human subjects (331; 73.6%). The majority of proposers were from UNS (309; 68.7%), were students (353; 78.4%), and had undergraduate education (166; 36.9%). The duration of the initial ethics review was generally <2 weeks (90.4%). Most (92.7%) protocols needed revision. The majority (66.4%) of proposers needed <2 weeks to revise the protocol. The total time for the entire ethics review process was 22.9 ± 14 days. Further evaluation found that the average duration needed for protocol revision was longer than that for reviewing (16 vs 9 days). It can be concluded that the ethics review process ran effectively so that almost all protocols submitted could undergo initial reviews in a relatively short time. The delayed ethical approval was due to the slow protocol revision process by the proposers.